On the role of helium metastable (23S1) measured by time resolved tunable diode laser spectroscopy in high current magnetron discharge. (1st December 2022) - Farsy, Abderzak El; Morel, Erwan; Rozier, Yoann; de Poucques, Ludovic; Robert, Jacques; Minea, Tiberiu
Abstract: Tunable diode laser absorption spectroscopy is applied to measure the density and gas temperature of helium metastable (2 3 S1 ) in the ionization region of magnetron discharge operated at very high current density ( > 10 A c m − 2 ), which is achievable in helium at 10 Pa with molybdenum target. Those measurements were combined to electrical characterization of the current and the voltage at the magnetron cathode. The discharge current waveform is anti-correlated with the time-evolution of helium metastable ( H e m ) density showing that the main depletion process of H e m is its ionization. Counterintuitively, the higher the gas temperature the lower the discharge peak current. Gas rarefaction and gas recycling are discussed as major contributors for this phenomenon in very high current glow discharge.